PENDIDIKAN INDONESIA PADA MASA PENDUDUKAN JEPANG 1942-1945 - Sholeha Sholeha; Elis Setiawati (Swarnadwipa, 2021)
The problem in this research is that education during the Japanese occupation experienced various challenges for the people of Indonesia. The aims of this study are: 1) To analyze and describe education in Indonesia during the Dutch colonial period 1900-1942; 2) To analyze and describe education in Indonesia during the Japanese occupation period 1942-1945; 3) To analyze and describe the driving and inhibiting factors of education in Indonesia during the Japanese occupation period 1942-1945. The research method uses historical methods, namely heuristics, literature study, source criticism, interpretation and historiography. Based on the results of the study, the education that was applied during the Dutch colonial period was given differently and was limited based on race/ethnic social position. Entering the era of Japanese occupation in Indonesia, the Dutch Colonial education system was then changed to semi-military education by applying physical training to students, military and strict indoctrination. Nevertheless, the Indonesian people get many opportunities in the field of education. Education organized by the Japanese military government in Indonesia has developed, through the simplification of the system, all levels of indigenous people are given the right to be able to access it, until Indonesian is used as the language of instruction. However, behind the development there are obstacles in it starting from the lack of educators, the lack of textbooks, the decreasing number of students attending school and the number of schools also decreasing very drastically. Education carried out during the colonial era did not pay attention to education in the context of humanity, but only to maintain one-sided power, political and economic interests.